2022
DOI: 10.1177/17448069221121307
|View full text |Cite
|
Sign up to set email alerts
|

Persistent inflammatory pain is linked with anxiety-like behaviors, increased blood corticosterone, and reduced global DNA methylation in the rat amygdala

Abstract: Chronic pain increases the risk of developing anxiety, with limbic areas being likely neurological substrates. Despite high clinical relevance, little is known about the precise behavioral, hormonal, and brain neuroplastic correlates of anxiety in the context of persistent pain. Previous studies have shown that decreased nociceptive thresholds in chronic pain models are paralleled by anxiety-like behavior in rats, but there are conflicting ideas regarding its effects on the stress response and circulating cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Although we found no significant effect of EE intervention in early adulthood on NMS mice, which is inconsistent with some reports, we found a certain improvement trend in the experiment, which may be caused by the short duration of EE intervention, and extending the duration of EE intervention may also achieve positive effects. In addition, previously studies shown that elevating levels of corticosterone increases anxiety-and depressionlike behaviors, induces visceral hypersensitivity, and decreases somatic pain thresholds (20)(21)(22)(23)(24). Consistent with this, preadult EE tended to normalize plasma corticosterone levels in NMS mice, whereas adult EE had no positive effect on plasma corticosterone reduction, suggesting that corticosterone plays an important role of EE in the improvement of visceral pain, anxiety, and depressive behaviors induced by NMS.…”
Section: Discussionsupporting
confidence: 74%
“…Although we found no significant effect of EE intervention in early adulthood on NMS mice, which is inconsistent with some reports, we found a certain improvement trend in the experiment, which may be caused by the short duration of EE intervention, and extending the duration of EE intervention may also achieve positive effects. In addition, previously studies shown that elevating levels of corticosterone increases anxiety-and depressionlike behaviors, induces visceral hypersensitivity, and decreases somatic pain thresholds (20)(21)(22)(23)(24). Consistent with this, preadult EE tended to normalize plasma corticosterone levels in NMS mice, whereas adult EE had no positive effect on plasma corticosterone reduction, suggesting that corticosterone plays an important role of EE in the improvement of visceral pain, anxiety, and depressive behaviors induced by NMS.…”
Section: Discussionsupporting
confidence: 74%
“…We thus probed whether ChR2 activation of ovBNST GA neurons could also alleviate anxiety-like behaviors in an inflammatory pain model. We used an intraplantar injection of complete Freund’s adjuvant (CFA), which is known to induce long-lasting inflammatory pain and anxiety-like behavior in animals 36,37 . Indeed, activation of ovBNST GA neurons in the CFA model resulted in increased exploration to the OF center and EPM and EZM open arms compared to control CFA-injected mice.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this study we focused on the effect of repeated intrathecal injections catalpol on the established pain behavior of CFA. In addition, previous studies have shown that chronic pain has the potential to increase the emergence of anxiety and produce symptoms of co-morbid anxiety in pain ( Shao et al, 2021 ; Farzinpour et al, 2022 ; Spinieli et al, 2022 ), so we investigated whether established persistent inflammatory pain induced by CFA can promote anxiety-like behavior in rats and whether catalpol alleviates after repeated treatment. This was confirmed by our results.…”
Section: Discussionmentioning
confidence: 99%